Rancang Bangun Sistem Informasi Manajemen Proyek Kolaborasi Kerja berbasis Mobile (Studi Kasus : Debox Indonesia) - Arif Hendrawan; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Projects are activities that are intended to produce products or services. In processing on the project, a management process is needed to complete the project. In software projects, there are several project management method one of which is Agile Project Management (APM) with Scrum framework. APM method are suitable for use in dynamic projects environments because of those high adaptability. Debox Indonesia company enganged in the field of software development also use APM methods to manage the project. The number of projects received makes Debox Indonesia often difficult to manage, because this company that only using Google Spreadsheets to manage their own project. So that information about project management and reporting becomes inaccurate. This research will implement a mobile-based system for project management based on the Agile Project Management Methodology with the Scrum framework and can also do project scrumming, reporting, and collaboration between employee. The system was built based on waterfall modeling and developed using React Native framework with javascript programming language and using GraphQL as middleware. Implementation of the system produces an information system that facilitates the project management process because every activity is recorded in the system. This research resulted in 67 functional and 1 nonfunctional requirement. During testing phase, the system was successfully tested with all valid results for all test cases, and mobile compatibility testing can be run on 6 different devices.